Mapping the elasticity of economic growth to financial development: A 1980 - 2012 empirical analysis for 100 countries - Zarzosa Valdivia, Fernando (2017)
Fil: Zarzosa Valdivia, Fernando. Universidad Nacional de Córdoba. Facultad de Ciencias Económicas; Argentina.